Development of Virtual Reality and Augmented Reality- Based Occupational Health and Safety Management Systems - Fadila Amanda Putri (IC-ITECHS, 2022)
In this time that has entered society 5.0, it is hoped that it can further improve the ability of human resources in their fields. The development of the Internet of Things, Big Data, and Artificial Intelligence can be a means of presenting new knowledge that is able to build life. The presence of a concept developed to form a super smart society has the aim of integrating virtual space and physical space as a solution to deal with various problems that remain focused on the humanitarian side. One of them is in the application of Occupational Health and Safety in the company, where in this case it requires a medium as a tool to convey information and provide education to workers within the company. The media is built in the form of a responsive mobile-based application that can display three-dimensional (3D) objects using VR and AR technology which is intended as a more interactive and immersive employee training method in implementing Occupational Health and Safety. Considering that there have been 177,000 cases of work accidents in Indonesia until 2020 based on data from the Social Security Organizing Agency (BPJS) of Employment. The purpose of this paper is to plan a strategy to overcome Occupational Health and Safety risks to achieve zero accidents. The writing of this scientific paper is descriptive analysis with a qualitative approach. The data sources used in the preparation of this scientific paper are primary data sources and secondary data sources with data collection techniques through literature studies and observations. The implementation of good Occupational Health and Safety can increase the level of productivity, in line with the statement that the application of Occupational Health and Safety in the workplace is a major effort in realizing a safe, comfortable, and healthy work environment and protecting and increasing the empowerment of healthy, safe, and high- performance workers. Implementing Occupational Health and Safety is a form of providing protection provisions for theworld of work, so as to minimize accidents in the workplace.